Bone age assessment using hand and clavicle x-ray images / Marjan Mansourvar - Mansourvar, Marjan (2014)
Bone age assessment (BAA) is a method for evaluating the level of skeletal maturity to estimate the actual age of a person. It is usually performed manually by comparing an X-ray image of a left hand-wrist with an atlas, which contains a collection of images of known persons in the clinical procedure. The manual methods are based on analyzing special regions of the images of the hand bones or the whole bones of the images. Both approaches are prone to observation variability, time-consuming, and decision made on bone age is subjective. As a result, there is a pressing need to develop an automated method for bone age assessment. This research aims to develop an automated system for bone age assessment using images of the hand and the clavicle. Our research uses a new image processing technique that involves generating the histogram of the X-ray images. This approach overcomes the image segmentation problem, and it also overcome problems when conducting BAA on people who have hand defects or even growth abnormalities in hand bone. The technique can also overcome the problem of handling noisy hand images by using the clavicle images. A questionnaire survey and interviews were conducted in the Faculty of Medicine in University of Malaya Medical Centre (UMMC), to get an overview of the implementation of BAA at UMMC and to gather the users’ requirements for the development of an automated BAA system. The system was developed based on the Analysis, Design, Development, Implementation and Evaluation (ADDIE) model. The automated system called BAASHC (bone age assessment system using hand and clavicle) was evaluated on its performance and user acceptance using the SUMI-based questionnaire. The results of evaluation show that our system is a reliable and highly accurate solution for bone age assessment. Overall, BAASHC is not only useful to radiologists and doctors in the daily clinical practice, but it can also be used in forensic investigations.